PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE QUIZTEAM UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI SMP NEGERI 5 PANJI SITUBONDO - Nawawi Agus Jaya (IKIP PGRI Jember, 2017)
The purpose of this study is to determine the increase in activity and learning outcomes of students through the application of active learning models Type Quiz Team on subjects IPS basic competencies describe the demand and supply and the form of class VIII Semester even in SMP Negeri 5 Panji Situbondo. Result of research, based on result of student learning at meeting of cycle II obtained data 2 student which not finished from 24 students who take the test, because student get less than 75 from score 100 and 22 students have finished classical reach 91,67% and student No Thoroughly 8.33%. Students' learning outcomes in cycle II have improved quite well when compared with the previous action and cycle I.